Set of Vectors for the Expression of Histidine-Tagged Proteins in Vaccinia Virus Recombinants - Inmaculada Galindo; María M. Lorenzo; Rafael Blasco (BioTechniques, 2001)
Vaccinia virus expression vectors are widely used to direct the expression of proteins in eukaryotic cells. Here, we describe a new set of plasmid vectors designed for the expression of histidine-tagged proteins in the vaccinia system. To facilitate the rapid isolation of virus recombinants, the plasmids contain a viral gene (F13L) that serves as an efficient selection marker based on virus plaque phenotype. Histidine codons and restriction sites derived from pET-16b bacterial expression plasmid were included, thus facilitating the transfer of genes between E. coli and vaccinia expression plasmids. Plasmids in which the gene is placed downstream of either a strong vaccinia virus or a T7 promoter were constructed, allowing for constitutive or conditional expression, respectively, of the foreign protein.